Cultural and Economic Aspect of Juju Dhau: A Survey Study on Societal Practices at Khwopa - Gosai, Saroj Raj (Khwopa Journal, 2024)
The traditional Nepalese delicacy Juju Dhau (known as “king yogurt” in Nepal Bhasa) holds a distinctive flavor and profound cultural significance, especially within the Newari communities of Bhaktapur. Traditionally crafted in clay pots that absorb moisture and insulated with rice husks, the preparation method has persisted across generations, preserving its unique taste and cultural relevance despite shifts in food preferences and advancements in dairy production technology. Beyond its culinary appeal, Juju Dhau has considerable economic value, contributing to Bhaktapur’s economy and providing employment opportunities for many locals. This delicacy has also transcended its traditional roots, gaining popularity among a broader audience and promoting Newari cultural heritage. Despite its significance, there has been limited academic exploration of Juju Dhau’s impact on both cultural identity and economic growth. This study addresses this gap by investigating how Newari cultural practices, exemplified by Juju Dhau, serve as a source of income for the local population. Employing field observations, document analysis, and interviews, the research underscores the critical role of cultural identity as both a symbol and a financial resource for the community.